2014
DOI: 10.1093/annonc/mdu239
|View full text |Cite|
|
Sign up to set email alerts
|

Capturing intra-tumor genetic heterogeneity by de novo mutation profiling of circulating cell-free tumor DNA: a proof-of-principle

Abstract: www.clinicaltrials.gov, NCT01090960.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
254
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(263 citation statements)
references
References 31 publications
6
254
0
3
Order By: Relevance
“…The very low allele frequency suggests that in some primary tumors ESR1 mutations pre-exist as rare clones, which are then selected for during metastatic progression. This is consistent with a previous study from a single patient, which used deep-targeted MPS and identified an ESR1 mutation (E380Q) at 2% allele frequency in primary disease and 68% in synchronous liver metastasis (25, 28). Detection of rare ESR1 mutations in primary tumors (0–7%) may be clinically relevant for predicting resistance to hormone therapy; however, additional studies using sensitive detection technologies are necessary to develop this area of investigation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The very low allele frequency suggests that in some primary tumors ESR1 mutations pre-exist as rare clones, which are then selected for during metastatic progression. This is consistent with a previous study from a single patient, which used deep-targeted MPS and identified an ESR1 mutation (E380Q) at 2% allele frequency in primary disease and 68% in synchronous liver metastasis (25, 28). Detection of rare ESR1 mutations in primary tumors (0–7%) may be clinically relevant for predicting resistance to hormone therapy; however, additional studies using sensitive detection technologies are necessary to develop this area of investigation.…”
Section: Discussionsupporting
confidence: 93%
“…The feasibility of using cfDNA to noninvasively identify molecular alterations within metastatic tumors has been shown in several studies (2426) and preliminary data suggest that cfDNA can be used to monitor breast cancer burden and treatment response (27). A recent proof-of-principle study detected an ESR1 mutation (E380Q) in cfDNA from a single patient with advanced hormone refractory breast cancer (25, 28). However, the detection of rare mutations has been challenged by several limiting factors, including low cfDNA yields and low tumor cellularity in metastatic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that ctDNA can detect intratumor and multitumor heterogeneity and detect complex patterns of treatment resistance. 5255 With the emergence of new sequencing modifications that improve sensitivity and decrease sequencing errors, we believe that ctDNA profiling by next-generation sequencing approaches will improve our understanding of tumor heterogeneity and patterns of somatic evolution in pediatric solid tumors. 12,16 In addition, the assays described in this study could facilitate broader profiling of ctDNA, such as deep whole-exome sequencing, by providing a mechanism to screen samples for the presence of sufficiently abundant ctDNA, allowing selection of samples most likely to yield informative data.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the derivative cell lines that were not detected in the BT474/ATCC parental cell line (BT474/ATCC-P) were defined using MuTect (28) for the single nucleotide variants, and a combination of Strelka and Varscan2 (29, 30) for insertions and deletions, with the BT474/ATCC-P line as the reference. SNVs and indels with mutant allelic fraction of less than 1% and/or supported by fewer than 5 reads were disregarded (31). Variants found with >5% global minor allele frequency in dbSNP (Build 137) or that were covered by <10 reads in the tumor or <5 reads in the BT474/ATCC-P cell line were disregarded.…”
Section: Methodsmentioning
confidence: 99%